Olfaction as a Marker of Cognitive Impairment in Older Veterans. (2nd January 2019) - Freimer, Daniel; Peltz, Carrie; Kaup, Allison; Xia, Feng; Yaffe, Kristine
Abstract: Olfactory testing may be an effective marker for cognitive impairment (CI) and dementia, but no studies have explored this association in older veterans, a vulnerable group with a high burden of chronic conditions. Independently living older veterans ( n = 59) completed a neuropsychological battery—assessing three cognitive domains: learning/memory, language, and executive function—and an olfactory identification (OI) assessment. Lower OI performance was significantly associated with worse memory and executive function ( p for trend = 0.03 and .05) after adjusting for age, education, smoking, and TBI history. Among older veterans, these results suggest that olfactory dysfunction may be a useful marker of CI.